Global Neurology: Navigating Career Possibilities - Schiess, Nicoline; Saylor, Deanna; Zunt, Joseph (Seminars in Neurology, 2018)
Neurology has not typically been associated with international relief work; however, with the growth of chronic cardiovascular disease and stroke associated with unhealthy eating and sedentary ways, the appearance of “new” neurologic diseases, such as the Zika and West Nile viruses, and the high numbers of seizure disorders resulting from neuroinfectious diseases, more opportunities are arising for international and globally oriented neurologists. Multiple opportunities exist for developing a global clinician–educator career pathway, including private institutions, nongovernmental organizations, government-funded opportunities such as Medical Education Partnership Initiative, Fogarty and Fulbright Scholarships, and the American Academy of Neurology's Global Health Section. Furthermore, increasing research capacity in developing countries and increased funding opportunities for global health research have led to new opportunities for neurologists to establish global health research careers. These opportunities could not have come at a better time, as many faculty members have noted a particularly strong interest in global neurology from medical students and residents. Career categories and opportunities for neurologists desiring to work globally are discussed along with the emerging “global neurologist” academic pathway.
Keywords: global neurology; global health neurology